Bahasa dan Identitas Kelompok dalam Pernyataan Tokoh Politik: Sebuah Studi Sosiolinguistik - Fadlilah, Afi; Utari, Rini; Iskandar, Denny (Sasdaya: Gadjah Mada Journal of Humanities, 2023)
This research aims to analyse the lingual forms of political figures' statements and their correlation to the speakers' identity from a sociolinguistic perspective. This research used a qualitative approach with descriptive data type. The object of this research is Megawati's statement in a live broadcast on the BKKBN Official YouTube account on 16 February 2023 in the event "Kick Off Pancasila in Action of the Universal Planning Movement to Prevent Stunting" and several political figures' speeches on social media. Data collection techniques in this study, namely by using documentation methods and literature studies. The results showed that language and political communication used by political figures can show the identity of a group. Communication patterns and speech code choices used by political figures when viewed from a sociolinguistic perspective are influenced by the relationship between participants and the situation that surrounds them. The results of the study can be used as additional insight into group identity identified from language use.